Herbal used as Epigenetic for Cancer Treatment - Navadiya, Kaushal B.; Goti, Bhautik D.; Raloliya, Utsav D.; Gamit, Kinjal S. (Journal for Research in Applied Sciences and Biotechnology, 2023)
Patterns of chromatin accessibility, which are in turn altered by epigenetic mechanisms, are responsible for determining the interactions that take place between transcription machinery, genes, and the cis-regulatory elements of those genes. Mutations that interfere with epigenetic processes frequently have the unfortunate side effect of causing cancer. Since these mutations can be undone, numerous anticancer treatments that target epigenetic pathways are now being developed and evaluated. (Cancer) is becoming more and more common everywhere. This decline in clinical outcomes is a result of a number of factors, including late diagnosis, a lack of efficient treatments for particular cancer subtypes, and drug resistance. Treatment resistance and stemness traits have been recognised as markers of this disease, and it has been demonstrated that epigenetic changes play a role in the process of cancer growth. Understanding these alterations and how they impact cancer carcinogenesis treatment is challenging but crucial. However, it may be able to provide the special knowledge needed to use these alterations as potential diagnostic, prognostic, therapeutic agents, and predictors of treatment efficacy. This underlines the importance of continued research to advance our knowledge of cancer carcinogenesis and epigenetics and help us overcome these challenges. This review aims to provide an overview of the state of the art in epigenetics research for cancer detection and treatment and to stimulate discussion on this subject.